Programming mechanoluminescent behaviors of 3D printed cellular structures. (1st December 2022) - Zhao, Jiayu; Song, Seongkyu; Mu, Xuan; Jeong, Soon Moon; Bae, Jinhye
Abstract: Mechanoluminescence (ML) materials enable the transformation of mechanical stimuli into optical signals. However, current ML devices have limited luminescent programmability and mechanical tunability due to the relatively simple geometries as restricted by the conventional fabrication techniques. Here, we develop a strategy that is applicable for various types of zinc sulfide (ZnS)-based phosphors for allowing the fabrication of ML elastomer into complex 2D or 3D geometries with periodic cellular structures. We demonstrate that different cellular structures with tunable mechanical properties enable programmable structure-dependent ML behaviors including anisotropic and isotropic luminescence. We further exploit the quantitative structure-stress-luminescence relationship, which provides fundamental knowledge support for designing next-generation ML-based stress sensors and wearable devices. Graphical Abstract: A granular mechanoluminescence (ML) elastomer ink is developed to enable the 3D printing of ML materials into complex 2D/3D cellular structures with different colors and programmed luminescent behaviors. The structure-dependent luminescence-stress relationships are explored by printed cellular structures and finite element analysis. Anisotropic and isotropic luminescence are achieved using cellular structures with positive and negative Poisson's ratios, respectively. ga1 Highlights: A granular mechanoluminescence elastomer network was developed for 3D printing. Cellular structures with single- and multi-color were 3D printed at high resolution. Programmable luminescence and mechanical properties were achieved. Structure-stress-luminescence relationships were quantitatively studied.